A method for preparing a cross-linked cellulose lignin-derived high-closed-pore hard carbon negative electrode material

The cross-linked cellulose lignin-derived high closed-pore hard carbon preparation addresses the structural issues of biomass hard carbon, enhancing sodium ion storage capacity and stability through controlled pore formation and reduced crystallinity.

CN118929635BActive Publication Date: 2024-12-24SICHUAN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411426462.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-24
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

Current biomass hard carbon negative electrode materials for sodium-ion batteries suffer from uncontrollable crystallinity, unstable pore structure, large specific surface area, and complex defect sites, leading to low coulomb first efficiency and reversible specific capacity, hindering their commercial development.

Method used

A method involving cross-linked cellulose lignin-derived high closed-pore hard carbon preparation, using microcrystalline cellulose and lignin modification, with processes like pre-carbonization, ball milling, and carbonization to regulate pore structure and surface chemical state, reducing crystallinity and increasing closed-pore content.

Benefits of technology

The method enhances the reversible capacity and cycle stability of the negative electrode material by forming a rich vortex closed-pore structure, promoting sodium ion storage and improving interlayer spacing for efficient deintercalation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118929635B_ABST
    Figure CN118929635B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a cross-linked cellulose lignin-derived high-closed-pore hard carbon negative electrode material, and relates to the technical field of sodium ion negative electrode materials; the preparation method comprises the following steps: (1) dispersing microcrystalline cellulose in an alkaline system, adding lignin under mechanical stirring conditions, then adding epichlorohydrin under water bath conditions and continuing stirring, then adding ethanol solution and stirring and regenerating, filtering, washing and vacuum drying to obtain a cross-linked cellulose lignin solid; (2) subjecting the cross-linked cellulose lignin solid to dehydroxylation polycondensation treatment, then ball milling and vibration screening to obtain a solid powder; (3) carbonizing the solid powder, then ball milling and vibration screening to obtain a cross-linked cellulose lignin-derived high-closed-pore hard carbon negative electrode material. The hard carbon material of the invention has a lower crystallinity, and the long-range ordered graphitized layer is broken, forming more short-range ordered pseudo-graphitized layers, generating a rich vortex closed-pore structure, which is beneficial to the storage of sodium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion negative electrode materials, and in particular to a method for preparing a cross-linked cellulose lignin-derived high-closed-pore hard carbon negative electrode material. Background Art

[0002] In recent years, sodium-ion batteries, as an emerging energy storage technology, are considered to be a powerful supplement and potential substitute for lithium-ion batteries due to their advantages such as abundant resources, low cost and environmental friendliness. In the research of sodium-ion batteries, the performance of the negative electrode material has a crucial influence on the electrochemical performance of the entire battery system. The current negative electrode materials mainly include carbon-based materials, titanium-based materials, alloy materials and metal compound materials. Carbon-based materials have attracted attention due to their low specific surface area and good conductivity, but the specific capacity and rate performance of many carbon-based negative electrode materials still need to be improved.

[0003] Hard carbon materials are considered to be one of the ideal materials for negative electrode materials of sodium ion batteries due to their unique pseudo-graphitized microstructure, high specific capacity, high charge and discharge rate performance, long cycle life, low sodium storage voltage and other excellent electrochemical properties. Hard carbon derived from biomass has the advantages of abundant resources, low cost, and environmental friendliness as negative electrode materials for sodium ion batteries. It is one of the hard carbon materials that are currently being studied more. However, biomass hard carbon has structural differences such as uncontrollable hard carbon crystallinity, unstable pore structure, large specific surface area, and complex defect sites, which lead to low coulomb first efficiency and low reversible specific capacity, which seriously hinders the commercial development of biomass hard carbon. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a method for preparing a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material, using microcrystalline cellulose as the main body and adopting a cross-linked lignin modification method to prepare a low crystallinity, controllable sp 2 Hybridized carbon and sp 3 The hard carbon negative electrode material with a hybrid carbon ratio has a lower degree of crystallinity, and the long-range ordered graphitized layer is broken, forming more short-range ordered pseudo-graphitized layers, generating a rich vortex closed-pore structure, which is beneficial to the storage of sodium ions.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material is provided, comprising the following steps:

[0006] (1) Dispersing microcrystalline cellulose in an alkaline system, adding lignin under mechanical stirring until completely dispersed, then adding epichlorohydrin under water bath conditions and continuing to stir, then adding ethanol solution and stirring to regenerate, and finally filtering, washing and vacuum drying in sequence to obtain cross-linked cellulose lignin solid;

[0007] (2) subjecting the cross-linked cellulose lignin solid obtained in step (1) to dehydroxylation polycondensation in a vacuum tube furnace into which argon gas is introduced, and then subjecting the solid to ball milling and vibration screening to obtain a solid powder;

[0008] (3) The solid powder obtained in step (2) is carbonized in a vacuum tube furnace into which argon gas is introduced, and then ball-milled and vibrated to obtain a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material.

[0009] Furthermore, in step (1), the alkaline system is prepared by dissolving an alkaline substance and urea in water; the alkaline substance is sodium hydroxide or ammonia water.

[0010] Furthermore, in the alkaline system, the mass volume ratio of the alkaline substance, urea and water is 30 g:24 g:300 mL.

[0011] Furthermore, in step (1), the mass ratio of microcrystalline cellulose to lignin is 18:2, 10:10 or 2:18.

[0012] Furthermore, in step (1), the mass volume ratio of the alkaline system, epichlorohydrin and ethanol solution is 300 mL: 9-12 mL: 300 mL.

[0013] Furthermore, in step (1), an ethanol solution with a concentration of 80 wt% is added and stirred for regeneration.

[0014] Furthermore, in step (1), the product is washed with ethanol and deionized water three times respectively, and dried in vacuum at 100°C for 24 hours.

[0015] Furthermore, in step (2), during the dehydroxylation polycondensation treatment, the temperature is first increased from 25°C to 180°C at a rate of 5°C / min, held for 90 min, then increased from 180°C to 320°C at a rate of 3°C / min, held for 24 h, then decreased in one step to 50°C at a rate of 5°C / min, and naturally cooled to room temperature.

[0016] Furthermore, in step (2), ball milling is performed for 1-2 h, and vibration screening is performed twice, and the particle size is 30-40 μm.

[0017] Furthermore, in step (3), during carbonization, the temperature is first increased from 25°C to 400°C at 5°C / min, then increased to 1300°C at 3°C / min, maintained for 120 min, then decreased to 400°C at 3°C / min, and finally decreased to 50°C at 5°C / min, and naturally cooled to room temperature.

[0018] Further, in step (3), ball milling is performed for 1-3 h.

[0019] Furthermore, in step (2) and step (3), the purity of argon gas is 99.99%.

[0020] The present invention has the following beneficial effects:

[0021] 1. The present invention uses microcrystalline cellulose as the main component and adopts a cross-linked lignin modification method to prepare a sp 2 Hybridized carbon and sp 3 Hard carbon negative electrode material with a hybrid carbon ratio; the process of pre-carbonization, ball milling, screening and re-carbonization is adopted to regulate the pore structure and surface chemical state of the hard carbon material, effectively reduce the specific surface area of ​​the negative electrode material, and make the particle size distribution more uniform, which is conducive to the penetration of the electrolyte, thereby improving the reversible capacity and cycle stability; the hard carbon material has lower crystallinity, and the long-range ordered graphitized layer is broken, forming more short-range ordered pseudo-graphitized layers, generating rich vortex closed-pore structure, which is conducive to the storage of sodium ions. At the same time, the interlayer spacing is increased, which is helpful for the deintercalation of sodium ions during the charge and discharge process, providing new ideas for the research of hard carbon negative electrode materials with high closed-pore sodium storage.

[0022] 2. The present invention uses renewable biomass microcrystalline cellulose and lignin as precursors, and uses epichlorohydrin as a cross-linking agent to prepare cross-linked cellulose lignin hard carbon, which reduces the crystallinity of the raw materials and regulates the sp 2 Hybridized carbon and sp 3 The proportion of hybrid carbon inhibits the growth of long-range ordered graphite layers and constructs a rich closed-pore structure.

[0023] 3. The present invention adopts the process of pre-carbonization, ball milling, screening, carbonization, ball milling and screening to regulate the pore structure and surface chemical state of the hard carbon material, effectively reduce the specific surface area of ​​the negative electrode material, make the particle size distribution more uniform, and thus improve the reversible capacity and cycle stability; pre-carbonization at 320 ° C can better promote the slow polycondensation process of hard carbon and effectively remove the hydroxyl group; the first ball milling and screening can make the particle size more uniform and reduce the specific surface area; carbonization at 1300 ° C can better carry out the aromatization process to form nanographite sheets, and with the sp 2 Hybridized carbon and sp 3 The proportion of hybrid carbon is regulated, the proportion of graphitized carbon is reduced, and the proportion of amorphous carbon is increased, showing more short-range ordered pseudo-graphitized domains, which promotes the formation of closed pores; secondary ball milling screening further screens hard carbon particles with uniform particle size, which is beneficial to the penetration of electrolyte.

[0024] 4. The surface of the cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material of the present invention is rougher, which is conducive to the penetration of the electrolyte; at the same time, with the increase of lignin content, the specific surface area of ​​the negative electrode material is significantly reduced, and the closed-pore content per unit mass increases, which is conducive to filling and storing sodium; and the interlayer spacing increases, which can promote the effective deintercalation of sodium ions. The cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material prepared by the present invention mainly stores sodium in closed pores, improves the reversible specific capacity, has excellent rate performance, and good cycle stability, which provides a new idea for the research of hard carbon negative electrode materials for sodium ion batteries with high closed-pore sodium storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Figure 1 is a scanning electron microscope image of the product obtained in Example 1 to Example 3; Figure a is a scanning electron microscope image of the product obtained in Example 1, Figure b is a scanning electron microscope image of the product obtained in Example 2, and Figure c is a scanning electron microscope image of the product obtained in Example 3;

[0026] Figure 2 The nitrogen adsorption / desorption images of the products obtained in Examples 1 to 3 are shown;

[0027] Figure 3 TEM images of the products obtained in Examples 1 to 3;

[0028] Figure 4 XRD, Raman and XPS images of the products obtained in Examples 1 to 3; Figure a is the XRD spectrum, Figure b is the Raman spectrum, Figure c is the XPS total spectrum, and Figure d is the XPS fine C spectrum image;

[0029] Figure 5 Figure 1 is a graph showing the constant current charge and discharge, rate and cycle performance of a half-cell; Figure a is a constant current charge and discharge curve of a half-cell, Figure b is a reference graph showing the slope capacity / platform capacity of the second cycle, Figure c is a rate performance graph, and Figure d is a cycle performance graph;

[0030] Figure 6 It is a half-cell constant current intermittent titration curve and a graph showing the relationship between the sodium ion diffusion coefficient and the voltage;

[0031] Figure 7 These are pictures of the constant current charge and discharge, rate and cycle performance of the full battery; Figure a is a schematic diagram of the full battery cycle experiment, Figure b is the constant current charge and discharge curve, and Figure c is the cycle performance diagram. DETAILED DESCRIPTION

[0032] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. Example

[0033] A method for preparing a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material comprises the following steps:

[0034] (1) Disperse 18 g of microcrystalline cellulose in 300 mL of alkaline system (30 g of sodium hydroxide / 24 g of urea), add 2 g of lignin under mechanical stirring until completely dispersed, then add 9 mL of epichlorohydrin in a 50 °C water bath and continue stirring for 30 min, then add 300 mL of 80 wt% ethanol solution and stir for regeneration, filter, wash with ethanol and deionized water three times respectively, and vacuum dry at 100 °C for 24 h to obtain cross-linked cellulose lignin solid;

[0035] (2) The cross-linked cellulose lignin solid obtained in step (1) was subjected to dehydroxylation polycondensation treatment in a vacuum tube furnace with argon gas, firstly heated from 25°C to 180°C at a rate of 5°C / min, held for 90 min, then heated from 180°C to 320°C at a rate of 3°C / min, held for 24 h, then cooled to 50°C in one step at a rate of 5°C / min, cooled naturally to room temperature, ball milled for 2 h, and vibrated and sieved twice to obtain a solid powder (30-40 μm);

[0036] (3) The solid powder obtained in step (2) was carbonized in a vacuum tube furnace with argon gas, firstly heated from 25 °C to 400 °C at 5 °C / min, then heated to 1300 °C at 3 °C / min, maintained for 120 min, then cooled to 400 °C at 3 °C / min, and finally cooled to 50 °C at 5 °C / min, cooled naturally to room temperature, ball milled for 2 h, and vibrated and sieved to obtain a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material, recorded as MC-LG-18-2. Example

[0037] A method for preparing a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material comprises the following steps:

[0038] (1) Disperse 10 g of microcrystalline cellulose in 300 mL of alkaline system (30 g of sodium hydroxide / 24 g of urea), add 10 g of lignin under mechanical stirring until completely dispersed, then add 10 mL of epichlorohydrin in a 50 °C water bath and continue stirring for 30 min, then add 300 mL of 80 wt% ethanol solution and stir for regeneration, filter, wash with ethanol and deionized water three times respectively, and vacuum dry at 100 °C for 24 h to obtain cross-linked cellulose lignin solid;

[0039] (2) The cross-linked cellulose lignin solid obtained in step (1) was subjected to dehydroxylation polycondensation treatment in a vacuum tube furnace with argon gas, firstly heated from 25°C to 180°C at a rate of 5°C / min, held for 90 min, then heated from 180°C to 320°C at a rate of 3°C / min, held for 24 h, then cooled to 50°C in one step at a rate of 5°C / min, cooled naturally to room temperature, ball milled for 2 h, and vibrated and sieved twice to obtain a solid powder (30-40 μm);

[0040] (3) The solid powder obtained in step (2) was carbonized in a vacuum tube furnace with argon gas, firstly heated from 25 °C to 400 °C at 5 °C / min, then heated to 1300 °C at 3 °C / min, maintained for 120 min, then cooled to 400 °C at 3 °C / min, and finally cooled to 50 °C at 5 °C / min, cooled naturally to room temperature, ball milled for 2 h, and vibrated and sieved to obtain a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material, recorded as MC-LG-10-10. Example

[0041] A method for preparing a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material comprises the following steps:

[0042] (1) Disperse 2 g of microcrystalline cellulose in 300 mL of alkaline system (30 g of sodium hydroxide / 24 g of urea), add 18 g of lignin under mechanical stirring until completely dispersed, then add 9 mL of epichlorohydrin in a 50 °C water bath and continue stirring for 30 min, then add 300 mL of 80 wt% ethanol solution and stir for regeneration, filter, wash with ethanol and deionized water three times respectively, and vacuum dry at 100 °C for 24 h to obtain cross-linked cellulose lignin solid;

[0043] (2) The cross-linked cellulose lignin solid obtained in step (1) was subjected to dehydroxylation polycondensation treatment in a vacuum tube furnace with argon gas, firstly heated from 25°C to 180°C at a rate of 5°C / min, held for 90 min, then heated from 180°C to 320°C at a rate of 3°C / min, held for 24 h, then cooled to 50°C in one step at a rate of 5°C / min, cooled naturally to room temperature, ball milled for 2 h, and vibrated and sieved twice to obtain a solid powder (30-40 μm);

[0044] (3) The solid powder obtained in step (2) was carbonized in a vacuum tube furnace with argon gas, firstly heated from 25 °C to 400 °C at 5 °C / min, then heated to 1300 °C at 3 °C / min, maintained for 120 min, then cooled to 400 °C at 3 °C / min, and finally cooled to 50 °C at 5 °C / min, cooled naturally to room temperature, ball milled for 2 h, and vibrated and sieved to obtain a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material, recorded as MC-LG-2-18.

[0045] Test Example 1:

[0046] The scanning electron microscope images of the cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode materials obtained in Examples 1 to 3 were obtained respectively. Figure 1 As shown; nitrogen adsorption / desorption pictures are shown Figure 2 As shown in the transmission electron microscope picture Figure 3 As shown, XRD, Raman and XPS images are as follows Figure 4 As shown in the figure, MCHCs represents cellulose hard carbon and LGHCs represents lignin hard carbon.

[0047] Depend on Figure 1 It can be seen that after cross-linking modification, the surface roughness of the hard carbon negative electrode material increases, indicating that the crystallinity decreases, which facilitates the transmission of sodium ions and thus improves the electrochemical performance of the hard carbon negative electrode.

[0048] Depend on Figure 2 It can be seen that after two screening treatments, the specific surface area of ​​the hard carbon is reduced, the pore size distribution is uniform, the surface defect sites are reduced, and the irreversible defect adsorption of sodium storage is inhibited.

[0049] Depend on Figure 3 It can be seen that as the proportion of cross-linked lignin increases, the degree of graphitization of the hard carbon negative electrode material decreases, the long-range ordered graphite layer is broken, and a short-range ordered pseudo-graphitization domain is formed, and a closed-pore structure is formed by the curling of short-range graphite sheets. Among them, MC-LG-10-10 hard carbon shows significantly more closed-pore structures, which is conducive to the formation of closed-pore sodium storage and improves the platform sodium storage capacity.

[0050] Depend on Figure 4 It can be seen that the XRD spectrum shows that the interlayer spacing d 002 The value increased from 0.373 nm to 0.398 nm, indicating that the degree of graphitization decreased and the interlayer spacing increased, which is conducive to the deintercalation of sodium ions. The ratio of graphitized carbon to amorphous carbon can be obtained by peak fitting of the Raman spectrum. D1 / I GThe results show that with the increase of cross-linked lignin content, the sp of cross-linked cellulose lignin hard carbon decreases from 1.48 to 1.14, indicating that the surface defects of hard carbon materials decrease and the degree of pseudo-graphitization increases. XPS images further prove that through the cross-linking reaction, the sp 2 Hybridized carbon ratio decreases, sp 3 As the proportion of hybridized carbon increases, it can be seen that the internal structure tends to be short-range ordered.

[0051] Test Example 2:

[0052] Half-cell assembly and testing, the specific steps are as follows:

[0053] (1) Preparation of negative electrode sheets: 0.8 g of the cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material obtained in Examples 1 to 3, 0.1 g of conductive carbon black (hereinafter referred to as Super P), and 3.33 g of 3.0 wt% polyvinylidene fluoride / N-methylpyrrolidone solution were weighed and ground evenly in a mortar, coated on a smooth aluminum foil surface using a 100 μm four-sided preparation device, placed in a vacuum drying oven at 80 ° C for 12 h, and cut into circular negative electrode sheets using a cutting machine with a diameter specification of 6 mm;

[0054] (2) Preparation of positive electrode sheets: Using metallic sodium as the standard positive electrode, first use a roller press to press the sheets to a thickness of 0.8 mm, and then cut the circular sodium sheets into 12 mm diameter sheets;

[0055] (3) Assemble button-type half-cell: positive electrode shell, spring, gasket, sodium sheet, glass fiber diaphragm, about 1mL sodium hexafluorophosphate electrolyte, negative electrode sheet, negative electrode shell, assembled from bottom to top. All assembly processes are carried out in a glove box continuously filled with argon (O2 concentration ≤ 0.5 ppm, H2O concentration ≤ 0.1 ppm).

[0056] The above half-cell was subjected to constant current charge and discharge, rate performance, cycle performance, and mass transfer kinetics tests. Figure 5 As shown, the constant current intermittent titration picture and Na + The relationship between the diffusion coefficient and voltage is shown in the figure Figure 6 shown.

[0057] Depend on Figure 5It can be seen that the constant current charge and discharge results show that the sodium storage capacity of the cross-linked hard carbon is significantly increased, and the first coulomb efficiency increases from 67% to 78%. From the slope capacity / platform capacity reference graph, it can be seen that the slope capacity of the cross-linked cellulose lignin-derived high closed-pore hard carbon shows a downward trend, and the platform capacity increases, which proves that the reduction of crystallization and the formation of closed pores are conducive to the improvement of sodium storage performance. In addition, the higher closed-pore content of MC-LG-10-10 creates its excellent electrochemical performance. From its rate curve, it can be seen that the higher the specific capacity at high current, the better the capacity retention rate, indicating that the rate performance is better. From the cycle capacity curve, it can be seen that the cross-linked cellulose lignin-derived high closed-pore hard carbon has good cycle stability. After 600 cycles, the capacity retention rate is about 74.8%.

[0058] Depend on Figure 6 It can be seen that the diffusion coefficient of high closed-pore hard carbon derived from cross-linked cellulose lignin is relatively stable during the charge and discharge process, and the mass transfer is uniform. When the discharge voltage is less than 0.2V, the diffusion coefficient decreases suddenly and the mass transfer slows down, indicating that the formation of closed pores is beneficial to filling pores and storing sodium on the low-potential platform, thereby improving the electrochemical stability.

[0059] Test Example 3:

[0060] Full battery assembly and testing, the specific steps are as follows:

[0061] (1) Preparation of negative electrode sheets: 0.8 g of the cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material obtained in Examples 1 to 3, 0.1 g of Super P, and 3.33 g of 3.0 wt% polyvinylidene fluoride / N-methylpyrrolidone were weighed and dissolved in a mortar and ground until uniform, and coated on a smooth aluminum foil surface using a 100 μm four-sided preparation device, placed in a vacuum drying oven at 80 ° C for 12 h, and cut into circular negative electrode sheets using a cutting machine with a diameter specification of 6 mm;

[0062] (2) Preparation of positive electrode sheets: 0.8 g sodium vanadium phosphate (NVP), 0.1 g Super P, and 3.33 g 3.0 wt% polyvinylidene fluoride / N-methylpyrrolidone solution were weighed in turn and ground into a uniform mixture in a mortar. The mixture was coated on a smooth aluminum foil surface using a 100 μm four-sided preparation device, dried in a vacuum drying oven at 80 °C for 12 h, and cut into circular negative electrode sheets using a 6 mm diameter cutter.

[0063] (3) Assembly of button-type full battery: Assemble in the same order as step (3) of implementation example 2.

[0064] The full battery was first activated by cycling for 3 cycles at 0.1 C before subsequent charge and discharge cycle tests. Figure 7 shown.

[0065] Depend on Figure 7It can be seen that based on the excellent closed-pore structure and outstanding half-cell behavior of MC-LG-10-10 hard carbon, the specific capacity of the full cell NVP||MC-LG-10-10 is 227.1 mAh g -1 The coulombic first efficiency is 98%, and the capacity retention rate after 200 cycles is 88.23%. It has good stability and outstanding electrochemical performance.

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material, characterized in that: The following steps are involved: (1) Dispersing microcrystalline cellulose in an alkaline system, adding lignin under mechanical stirring until completely dispersed, then adding epichlorohydrin under water bath conditions and continuing stirring, then adding ethanol solution and stirring to regenerate, and finally filtering, washing and vacuum drying in sequence to obtain a cross-linked cellulose lignin solid; the alkaline system is prepared by dissolving an alkaline substance and urea in water; the alkaline substance is sodium hydroxide or ammonia water; (2) subjecting the cross-linked cellulose lignin solid obtained in step (1) to dehydroxylation polycondensation in a vacuum tube furnace into which argon gas is introduced, and then subjecting the resultant to ball milling and vibration screening to obtain a solid powder; (3) The solid powder obtained in step (2) is carbonized in a vacuum tube furnace into which argon gas is introduced, and then ball-milled and vibrated to obtain a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material.

2. The method for preparing the cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material according to claim 1, characterized in that: In the alkaline system, the mass volume ratio of the alkaline substance, urea and water is 30 g:24 g:300 mL.

3. The method for preparing the cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material according to claim 1, characterized in that: In step (1), the mass ratio of microcrystalline cellulose to lignin is 18:2, 10:10 or 2:

18.

4. The method for preparing the cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material according to claim 1, characterized in that: In step (1), the sample was washed with ethanol and deionized water for three times, respectively, and then dried in vacuum at 100 °C for 24 h.

5. The method for preparing the cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material according to claim 1, characterized in that: In step (2), during the dehydroxylation polycondensation treatment, the temperature is first increased from 25°C to 180°C at a rate of 5°C / min, held for 90 min, then increased from 180°C to 320°C at a rate of 3°C / min, held for 24 h, then cooled in one step to 50°C at a rate of 5°C / min, and naturally cooled to room temperature.

6. The method for preparing a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material according to claim 1, characterized in that: In step (2), ball milling is performed for 1-2 h, and vibration screening is performed twice, and the particle size is 30-40 μm.

7. The method for preparing a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material according to claim 1, characterized in that: In step (3), during carbonization, the temperature is first increased from 25°C to 400°C at 5°C / min, then increased to 1300°C at 3°C / min, maintained for 120 min, then decreased to 400°C at 3°C / min, and finally decreased to 50°C at 5°C / min, and naturally cooled to room temperature.

8. The method for preparing a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material according to claim 1, characterized in that: In step (3), ball milling is performed for 1-3 h.

9. The method for preparing a cross-linked cellulose lignin-derived high closed-pore hard carbon negative electrode material according to claim 1, characterized in that: In step (2) and step (3), the purity of argon gas is 99.99%.

Citation Information

Patent Citations

  • Preparation method of high-yield biomass hard carbon

    CN111717908A

  • Method for preparing battery negative electrode material by utilizing enzymatic hydrolysis lignin-based epoxy resin

    CN112408359A

  • Preparation method of high-yield biomass hard charcoal

    CN116281948A

  • Porous silicon carbon negative electrode material and preparation method and application thereof

    CN117038941A

  • Lignin-based hard carbon material, preparation method thereof and application of lignin-based hard carbon material in sodium-ion battery

    CN117902577A